Sarcoidosis-Like Reaction in Melanoma Patients Receiving Immunotherapy or Targeted Therapy - Giulia Murgia; Luca Valtellini; Gianluca Nazzaro; Emanuela Passoni; Federica Scarfì; Francesca Boggio; Angelo V. Marzano; Ornella Garrone; Nerina Denaro (Case Reports in Oncological Medicine)
This case series highlights the complexity of sarcoidosis-like reactions (SLRs) during cancer treatment, specifically in patients receiving immunotherapy or targeted therapies for melanoma. SLRs can either mimic disease progression or present as part of the clinical manifestation, making diagnosis and treatment challenging. Our study reviewed the medical records of 31 patients who were candidates for postoperative treatment between June 2022 and June 2024. Out of these, three patients developed SLRs during their treatment. A 55-year-old woman with Stage IIIb cutaneous melanoma, receiving adjuvant therapy with anti-PD-1, after seven cycles of pembrolizumab, developed mediastinal node enlargement and skin hypodermic nodes. A biopsy of the hypodermic node revealed granulomatous infiltrates with sparse lymphocytes, consistent with sarcoidosis. A low dose of steroids was administered, resulting in a dramatic improvement. A 48-year-old woman with Stage IIIb BRAF wild-type melanoma, receiving nivolumab every 4 weeks, developed systemic sarcoidosis after seven cycles, primarily affecting extrapulmonary sites. Despite the immune-induced sarcoidosis, her treatment was not stopped, as decided by the multidisciplinary team (MDT). A 65-year-old man with Stage IIIb BRAF-mutant melanoma, receiving dabrafenib and trametinib, developed lung and cutaneous sarcoidosis, presenting with symptoms that led to emergency department admission. In all cases, the MDT played a crucial role in determining the course of treatment and balancing the risks of continuing or suspending cancer therapies while managing SLRs. National and international guidelines were consulted, but tailored decisions by the MDT were essential for optimizing patient care.